A high-toughness soybean protein isolate composite film and preparation method thereof

Soy protein isolate and sodium lignin sulfonate were mixed under alkaline conditions by the flow-drip method, and a modifier was added to prepare a high-tough soy protein isolate composite membrane, which solved the problem of poor mechanical properties in the prior art, achieved significant improvement in mechanical properties and environmentally friendly and low-energy characteristics of the process.

CN118206784BActive Publication Date: 2025-03-18GUANGDONG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410232996.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-01
Publication Date
2025-03-18
Estimated Expiration
2044-03-01

AI Technical Summary

Technical Problem

The existing soy protein isolate plastics have poor mechanical properties, making it difficult to take into account both the break strength and the elongation of break. The traditional melting process is complex and the energy consumption is high, which limits its large-scale production application.

Method used

Soy protein isolate and sodium lignin sulfonate were mixed under alkaline conditions by flow-drip method, glycerin and urea were added for modification, and a high-tough soy protein isolate composite membrane was prepared by casting method.

Benefits of technology

It significantly improves the break strength and elongation of the soybean protein isolate composite membrane, has a mechanical performance that is close to traditional plastics, and has environmentally friendly processes and low energy consumption, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118206784B_ABST
    Figure CN118206784B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of green natural materials, and specifically to a high-toughness soy protein isolate composite film and a preparation method thereof. The method comprises the following steps: step 1, uniformly mixing soy protein isolate and sodium lignin sulfonate in deionized water, wherein the weight ratio of soy protein isolate to sodium lignin sulfonate is 15-25:1; step 2, adding NaOH solution to the mixture to adjust the pH to 8-10, and then adding glycerol; step 3, heating the mixture treated in step 2 in a water bath, stirring at 70-95°C for 0.5-1.5h, and then cooling the mixture naturally in the water bath until the temperature of the water bath drops to 35-50°C, adding urea, and obtaining a soy protein isolate solution; step 4, pouring the soy protein isolate solution into a mold by a casting method and controlling the thickness to obtain a soy protein isolate composite film, and the preparation method effectively improves the strength of the mutual connection between material molecules, and greatly improves the breaking strength and breaking elongation of the protein composite film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of green natural materials, and in particular to a high-toughness soybean protein isolate composite film and a preparation method thereof. Background Art

[0002] With the increasing global attention to sustainable development and environmental protection, the environmental impact of traditional plastic products has become increasingly prominent. Therefore, it is urgent to seek an environmentally friendly material that can replace traditional plastics. In the process of looking for alternatives to petroleum raw materials, people have found that if natural renewable resources are effectively used to synthesize the industrial production route of degradable materials, this is completely in line with the development route of sustainable and circular economy. Therefore, biodegradable plastics have gradually become a hot area of ​​research and application. As a non-petroleum, biodegradable and renewable resource, agricultural and sideline product plant protein has gradually received widespread attention. Bioplastics produced with agricultural and sideline product protein as raw materials are called "second-generation bioplastics" products.

[0003] Among them, soy protein isolate (SPI), as a natural polymer material, has good renewability, degradability and biocompatibility, and is widely used in the preparation of bio-based plastics. However, since protein-based bioplastics are mostly loose polypeptide structures, the water absorption, thermal stability and mechanical strength of protein-based bioplastics are relatively low compared with other common plastics. Existing technologies improve mechanical properties through chemical / physical modification, adding small molecule plasticizers, adding reinforcing materials, and using cross-linking agents for chemical cross-linking.

[0004] Chinese patent CN02115509.7 discloses a modified soybean protein plastic and a preparation method thereof, which discloses that calcium lignin sulfonate and soybean protein isolate are mechanically mixed in proportion, glycerol is added to plasticize and mix well, and then melt blended in an internal mixer at 140°C and 30rpm for 5 minutes, and then subjected to hot pressing to obtain a sheet. Although the patented technology can make the breaking strength of protein plastic reach 1.98Mpa and the elongation at break reach 133.8%, this is still far from the mechanical requirements of traditional plastics, and the breaking strength and elongation at break cannot be achieved at the same time, and the mechanical properties are poor. In addition, the patent uses a melting method to manufacture plastics, which has a complex process and high energy consumption, which is not conducive to large-scale production applications. Summary of the invention

[0005] One of the purposes of the present invention is to avoid the shortcomings of the prior art and provide a method for preparing a high-toughness soy protein isolate composite film. The preparation method uses a cast-through method to effectively improve the strength of the mutual connection between material molecules in an environmentally friendly and low-energy method, thereby greatly improving the breaking strength and breaking elongation of the protein composite film.

[0006] In order to achieve one of the above-mentioned invention purposes, the following technical solution is provided:

[0007] Provided is a method for preparing a high-toughness soy protein isolate composite film, comprising the following steps:

[0008] Step 1, mixing soy protein isolate and sodium lignin sulfonate in deionized water to obtain a mixed material, wherein the weight ratio of the soy protein isolate to the sodium lignin sulfonate is 15 to 25:1;

[0009] Step 2, adding NaOH solution to the mixture to adjust the pH to 8-10, and then adding glycerol, wherein the amount of glycerol added is 0.1-0.3 mL per gram of soy protein isolate;

[0010] Step 3: Heat the mixture after step 2 in a water bath, stir at 70-95°C for 0.5-1.5h, and then cool the mixture naturally in the water bath until the temperature of the water bath drops to 35-50°C, add urea, and add 0.1-0.3g of urea per gram of soy protein isolate.

[0011] Keep the water bath temperature at 35-50°C, stir and react for 0.6-1.5h to obtain a soy protein isolate solution;

[0012] Step 4: pouring the soy protein isolate solution into a mold by a casting method and controlling the thickness, and obtaining a soy protein isolate composite film after drying.

[0013] In some embodiments, the concentration of NaOH is 1-1.5 mol / L.

[0014] In some embodiments, in step 1, the weight ratio of the soy protein isolate to the sodium lignin sulfonate is 20:1.

[0015] In some embodiments, in step 2, the pH is 9, and the amount of glycerol added per gram of soy protein isolate is 0.2 mL.

[0016] In some embodiments, in step three, the mixture is stirred at a constant temperature of 90° C. for 1 hour, and the urea is added after the water bath is cooled to 45° C. The urea addition amount is 0.2 g per gram of soy protein isolate. The temperature of the water bath is maintained at 45° C. and the reaction is stirred for 1 hour to obtain a soy protein isolate solution.

[0017] In some embodiments, in step 4, the drying method is natural drying.

[0018] In some embodiments, the mold is a silicone mold.

[0019] The beneficial effects of the method for preparing a high-toughness soy protein isolate composite film of the present invention are as follows:

[0020] (1) The method for preparing a high-toughness soy protein isolate composite film of the present invention, wherein sodium lignin sulfonate is used as an anionic surfactant to disperse in water, thereby obtaining a homogeneous system, making sodium lignin sulfonate and soy protein have good compatibility, and avoiding the problem of single-phase aggregation in the film. Alkaline and urea conditions can modify the protein, allowing the protein peptide chain to unfold and expose more groups, thereby facilitating the improvement of the strength of the connection between molecules. In addition, when the pH is alkaline and in the presence of urea, the sodium lignin sulfonate surfactant is more likely to form micelles, thereby improving the modification effect of sodium lignin sulfonate on the protein, allowing the protein to stably form a folded / helical structure, and then making it easier for the protein peptide chain to interact with the micelles formed by sodium lignin sulfonate, so that the interaction between the protein and the micelles formed by sodium lignin sulfonate is a flexible helical micelle model, that is, Figure 3 The folded / helical structure of the protein shown wraps the loose micelles on the surface, and entanglement is formed between the protein and sodium lignin sulfonate, which effectively improves the mechanical properties of the composite film.

[0021] (2) The method for preparing the high-toughness soy protein isolate composite film of the present invention, wherein the molecular formula of sodium lignin sulfonate is as follows: Figure 2 As shown, there are various active groups in the organizational structure of sodium lignin sulfonate, which can produce condensation or hydrogen bonding with other compounds. Due to the introduction of sulfonic acid groups in the molecule, it has good water solubility and good chemical stability in aqueous solution, and has strong dispersibility. Since the charge of the interaction between protein and sodium lignin sulfonate depends on the number of charges on sodium lignin sulfonate, the sulfonic acid group and phenolic hydroxyl group in sodium lignin sulfonate can ionize more negative charges at pH 8-10, which can enhance the interaction between protein and sodium lignin sulfonate. In aqueous solution, the anions contained in sodium lignin sulfonate form ionic bonds with the cationic amino acids contained in the protein, and the aromatic groups contained in sodium lignin sulfonate form π-π conjugation with the aromatic structures contained in the amino acids of the protein, further enhancing the interaction between molecules, further improving the mechanical properties of the composite film, effectively improving the modulus and toughness of the composite film, and greatly improving the breaking strength and elongation at break of the protein composite film.

[0022] (3) The method for preparing a high-toughness soy protein isolate composite film of the present invention adopts a solution casting method to prepare a soy protein isolate composite material. The experimental method uses green natural materials, has simple operation steps and low energy consumption, and is easy to process and shape the composite material. The obtained biofilm has both strong toughness and high elasticity, and its mechanical properties are very close to those of traditional plastics, which is suitable for large-scale production and application.

[0023] A composite film is also provided, characterized in that it is prepared by the above-mentioned method for preparing the high-toughness soy protein isolate composite film. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the synthesis route of the method for preparing the high-toughness soy protein isolate composite film of the present invention.

[0025] Figure 2 It is the molecular formula of sodium lignin sulfonate.

[0026] Figure 3 This is a flexible helical micelle model of the protein and sodium lignin sulfonate combination of the present invention. In which, the blue protein chain surrounds and penetrates the central surfactant micelle; green represents carbon atoms, white represents hydrogen atoms, red represents oxygen atoms, orange represents sulfur, and yellow represents sodium.

[0027] Figure 4 1 is the tensile stress-strain curve of the soy protein isolate composite film of Examples 1 to 6 and Comparative Example 1.

[0028] Figure 5 The breaking strength and breaking elongation of the SPI / LS films with different LS contents in Examples 1 to 6 and Comparative Example 1 are shown.

[0029] Figure 6 are the modulus and toughness of the SPI / LS films with different LS contents of Examples 1 to 6 and Comparative Example 1.

[0030] Figure 7 This is a diagram of the mechanical properties of the composite film prepared by the melting method in Example 2.

[0031] Figure 8 It is the ultraviolet spectrophotometer test chart of the composite film of Example.

[0032] Fig. 9 It is a picture showing the effect of using the composite film of the embodiment to plant crops.

[0033] Fig.10 Graph showing the biodegradation effect of the composite membrane of the embodiment. DETAILED DESCRIPTION

[0034] The preferred embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although the preferred embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.

[0035] This embodiment discloses a method for preparing a high-toughness soy protein isolate composite film, comprising the following steps:

[0036] Step 1: Evenly mix the soy protein isolate and sodium lignin sulfonate in deionized water to obtain a mixed material, wherein the weight ratio of the soy protein isolate to the sodium lignin sulfonate is 15 to 25:1, preferably 20:1.

[0037] Step 2, adding NaOH solution to the mixture to adjust the pH to 8-10, preferably 9, and then adding glycerol, wherein the amount of glycerol added per gram of soy protein isolate is 0.1-0.3 mL, preferably 0.2 mL;

[0038] Step 3: heat the mixture after step 2 in a water bath, stir at 70-95°C for 0.5-1.5h, preferably at 80°C for 1h, and then cool the mixture naturally in the water bath until the temperature of the water bath drops to 35-50°C, preferably: add urea, the amount of urea added per gram of soy protein isolate is 0.1-0.3g, preferably 0.2g.

[0039] Keep the water bath temperature at 35-50° C., preferably 40° C., and stir the reaction for 0.6-1.5 h, preferably 1 h, to obtain a soy protein isolate solution;

[0040] Step 4: pouring the soy protein isolate solution into a mold by a casting method and controlling the thickness, and obtaining a soy protein isolate composite film after drying.

[0041] The concentration of NaOH is 1-1.5 mol / L, preferably 1.2 mol / L.

[0042] Example 1

[0043] The method for preparing the high-toughness soy protein isolate composite film disclosed in this embodiment is as follows: Figure 1 As shown, the following steps are included:

[0044] Step 1: Mix 2g of soy protein isolate, 0.1g (5wt%) sodium lignin sulfonate (LS) and 30mL of deionized water in a 50mL flask, place in a 90℃ water bath and stir, adjust the pH to 9 with sodium hydroxide solution, add 0.4mL of glycerol, and keep the temperature at 90℃ and stir for 1h. Then cool the water bath naturally.

[0045] Step 2: When the temperature in the water bath is cooled to 45°C, urea (0.4 g) is added for modification, and the mixture is stirred at a constant temperature of 45°C for 1 h;

[0046] Step 3: Pour the obtained soy protein isolate solution into a 10*10*0.8cm 3 The resulting mixture was placed in a silicone mold and dried naturally to obtain a soy protein isolate composite film (SPI / LS-5).

[0047] Example 2

[0048] The method for preparing the high-toughness soy protein isolate composite film disclosed in this embodiment comprises the following steps:

[0049] Step 1: Mix 2g of soy protein isolate, 0.2g (10wt%) sodium lignin sulfonate and 30mL of deionized water in a 50mL flask, place in a 90℃ water bath and stir, adjust the pH to 9 with sodium hydroxide solution, add 0.4mL of glycerol, and keep the temperature at 90℃ and stir for 1h. Then cool the water bath naturally.

[0050] Step 2: When the temperature in the water bath is cooled to 45°C, urea (0.4 g) is added for modification, and the mixture is stirred at a constant temperature of 45°C for 1 h;

[0051] Step 3: Pour the obtained soy protein isolate solution into a 10*10*0.8cm 3 The resulting mixture was placed in a silicone mold and dried naturally to obtain a soy protein isolate composite film (SPI / LS-10).

[0052] Example 3

[0053] The method for preparing the high-toughness soy protein isolate composite film disclosed in this embodiment comprises the following steps:

[0054] Step 1: Mix 2g of soy protein isolate, 0.3g (15wt%) sodium lignin sulfonate and 30mL of deionized water in a 50mL flask, place in a 90℃ water bath and stir, adjust the pH to 9 with sodium hydroxide solution, add 0.4mL of glycerol, and keep the temperature at 90℃ and stir for 1h. Then cool the water bath naturally.

[0055] Step 2: When the temperature in the water bath is cooled to 45°C, urea (0.4 g) is added for modification, and the mixture is stirred at a constant temperature of 45°C for 1 h;

[0056] Step 3: Pour the obtained soy protein isolate solution into a 10*10*0.8cm 3 The resulting mixture was placed in a silicone mold and dried naturally to obtain a soy protein isolate composite film (SPI / LS-15).

[0057] Example 4

[0058] The method for preparing the high-toughness soy protein isolate composite film disclosed in this embodiment comprises the following steps:

[0059] Step 1: Mix 2g of soy protein isolate, 0.4g (20wt%) sodium lignin sulfonate and 30mL of deionized water in a 50mL flask, place in a 90℃ water bath and stir, adjust the pH to 9 with sodium hydroxide solution, add 0.4mL of glycerol, and stir at 90℃ for 1h. Then cool the water bath naturally.

[0060] Step 2: When the temperature in the water bath is cooled to 45°C, urea (0.4 g) is added for modification, and the mixture is stirred at a constant temperature of 45°C for 1 h;

[0061] Step 3: Pour the obtained soy protein isolate solution into a 10*10*0.8cm 3 The resulting mixture was placed in a silicone mold and dried naturally to obtain a soy protein isolate composite film (SPI / LS-20).

[0062] Example 5

[0063] The method for preparing the high-toughness soy protein isolate composite film disclosed in this embodiment comprises the following steps:

[0064] Step 1: Mix 2 g of soy protein isolate, 0.5 g (25 wt%) sodium lignin sulfonate and 30 mL of deionized water in a 50 mL flask, place in a 90°C water bath and stir, adjust the pH to 9 with sodium hydroxide solution, add 0.4 mL of glycerol, and stir at 90°C for 1 h. Then cool the water bath naturally.

[0065] Step 2: When the temperature in the water bath is cooled to 45°C, urea (0.4 g) is added for modification, and the mixture is stirred at a constant temperature of 45°C for 1 h;

[0066] Step 3: Pour the obtained soy protein isolate solution into a 10*10*0.8cm 3 The resulting mixture was placed in a silicone mold and dried naturally to obtain a soy protein isolate composite film (SPI / LS-25).

[0067] Example 6

[0068] The method for preparing the high-toughness soy protein isolate composite film disclosed in this embodiment comprises the following steps:

[0069] Step 1: Mix 2g of soy protein isolate, 0.6g (30wt%) sodium lignin sulfonate and 30mL of deionized water in a 50mL flask, place in a 90℃ water bath and stir, adjust the pH to 9 with sodium hydroxide solution, add 0.4mL of glycerol, and stir at 90℃ for 1h. Then cool the water bath naturally.

[0070] Step 2: When the temperature in the water bath is cooled to 45°C, urea (0.4 g) is added for modification, and the mixture is stirred at a constant temperature of 45°C for 1 h;

[0071] Step 3: Pour the obtained soy protein isolate solution into a 10*10*0.8cm 3 The resulting mixture was placed in a silicone mold and dried naturally to obtain a soy protein isolate composite film (SPI / LS-30).

[0072] Comparative Example 1

[0073] Step 1: Mix 2g of soy protein isolate (SPI) with 30mL of deionized water in a 50mL flask, place in a 90℃ water bath, stir, adjust the pH to 9, add 0.4mL of glycerol, and keep the temperature at 90℃ and stir for 1h. Then cool the water bath naturally.

[0074] Step 2: When the temperature in the water bath is cooled to 45°C, urea (0.4 g) is added for modification, and the mixture is stirred at a constant temperature of 45°C for 1 h;

[0075] Step 3: Pour the obtained soy protein isolate solution into a 10*10*0.8cm 3 The soy protein isolate film was obtained by placing the soy protein isolate film in a silicone mold and drying it naturally.

[0076] Comparative Example 2

[0077] This comparative example discloses a method for preparing a high-toughness soy protein isolate composite film, comprising the following steps:

[0078] 2g of soy protein isolate was mixed with 0.3g (15wt%) sodium lignin sulfonate, glycerol was added for plasticization, and melt blending was performed in an internal mixer at 120-150°C and 10-80rpm for 3-10 minutes; then hot pressing was performed at 130-180°C and 10-30MPa to obtain a sheet.

[0079] Effect verification

[0080] Composite membrane performance test

[0081] The composite films obtained in the examples and comparative examples were tested for performance. The test method was based on GB / T13022-1991 standard. A universal testing machine (Inspekt Table Blue 5KN) was used to perform a tensile test on the prepared bioplastics. The sample size was 100×20 mm, the test rate was 30 mm / min, and the test gauge length was 25 mm. The test data was recorded. Each sample was tested 5 times under the same conditions. The average value of the 5 tests was taken as the test result. The data was analyzed to obtain the following:

[0082] Figure 4 The tensile stress-strain curves of the soy protein isolate composite films of Examples 1 to 6 and Comparative Example 1 show that the stress-strain changes of the soy protein isolate composite materials with different amounts of sodium lignin sulfonate are not the same. When the content of sodium lignin sulfonate is 10wt%, the breaking strength reaches a maximum value of 15MPa, and the elongation at break also reaches 280%, and the composite film shows excellent mechanical properties. When the content of sodium lignin sulfonate exceeds 10wt%, the breaking strength and elongation at break gradually decrease. And, from Figure 4 It can be seen that in comparative example 1, the amount of sodium lignin sulfonate added is 0, and its breaking strength and breaking elongation are the lowest. It can be seen that when sodium lignin sulfonate is added in the present application and the addition amount is 10%, the composite film can obtain significant breaking strength and breaking elongation.

[0083] like Figure 5 As shown, the breaking strength and breaking elongation of SPI / LS films with different LS contents, Figure 5 After many experiments, it was found that 5% elongation at break was the best, but the corresponding breaking strength was not good. As the LS content increased, 10% breaking strength was the highest and also had excellent elongation at break.

[0084] Figure 6 The modulus and toughness of the SPI / LS films with different LS contents in Examples 1 to 6 and Comparative Example 1 show that the modulus and toughness of the soy protein isolate composites with different sodium lignin sulfonate contents are different. When the content of sodium lignin sulfonate is 10wt%, the modulus reaches a maximum value of 100MPa and the toughness reaches 33MJ / m 3 The composite film showed excellent mechanical properties. When the content of sodium lignin sulfonate exceeded 10wt%, the modulus and toughness gradually decreased. Figure 6 It can be seen that in Comparative Example 1, the addition amount of sodium lignin sulfonate is 0, and its modulus and toughness are the lowest. It can be seen that when the sodium lignin sulfonate is added in the present application and the addition amount is 10%, the composite film can obtain significant modulus and toughness.

[0085] Figure 7 Comparative Example 2 shows that the composite film prepared by the melt method has an elongation at break of 7.5%, a fracture strength of 7 MPa, and a toughness of 0.27 MJ / m 3 , the modulus is 131MPa. It can be seen that the mechanical properties of the composite film prepared by the melt method are significantly lower than those of the composite film prepared by the cast method of the present invention (elongation at break is 280%, breaking strength is 15MPa, and toughness is 30MJ / m 3 , modulus is 100MPa). It can be seen that the cast-through method of the present application can prepare a composite film with excellent mechanical properties.

[0086] Figure 8 As shown in the figure, the UV spectrophotometer test shows that the SPI / LS composite film of the embodiment gradually increases with the continuous increase of LS addition. The transmittance of the composite film in the wavelength range of 400-600nm is greatly reduced, and the transmittance below 400nm is almost zero, indicating that it has excellent UV shielding performance. This is because the sodium lignin sulfonate contains an aromatic structure, which has a strong shielding effect on ultraviolet rays.

[0087] Fig. 9 As shown, the composite film was covered in a commercial seedling pot, and the germination rate of seeds in the seedling pot of the protein-based composite material of the embodiment was compared with that of the commercial PE film. Fig. 9 As shown in the figure, the germination rate of pepper and tomato seeds after three weeks of coverage with PE film and SPI / LS composite film with different LS contents. With the increase of LS content, the germination rate of seeds is better than that of commercial PE film. This is due to the excellent UV shielding effect of the composite film, and the darker color of the film can absorb more energy, so that the soil temperature remains stable, which is more conducive to the germination and growth of seeds. In order to test the universality of the film, the film was also used to test radish and wheat seeds. After three weeks, it can still be observed that the composite film has the same or even better effect as the PE film, indicating that the composite film has a positive effect on seed germination.

[0088] Fig.10 As shown, the composite membrane of the embodiment was cut into a 6*6cm square shape and buried in 10cm deep moist soil. The samples were taken out and photographed every 7 days to observe the degradation process. After 7 days, white colonies appeared on the surface of the composite membrane. At this time, the composite membrane still had certain mechanical properties. After 14 days, the surface of the composite membrane was completely occupied by colonies. The SPI and SPI / LS-5 composite membranes had been degraded, while the other composite membranes had completely lost their mechanical properties. This shows that the material has good biodegradability.

[0089] In this application, sodium lignin sulfonate (LS), a waste derivative of the papermaking industry, is compounded with soy protein isolate (SPI) in an alkaline solution, urea is used to modify the protein, glycerol is used as a plasticizer, and the SPI / LS composite material is obtained after natural drying. SPI and LS interact with each other through ionic interactions, hydrogen bonds and hydrophobic interactions. In addition, sodium lignin sulfonate exhibits micellar behavior in aqueous solution, forming micelles with loose surfaces, forming molecular entanglements with the three-dimensional structure of proteins, and at the same time, lignin can induce the secondary structure of protein chains to tend to a more stable β-folded structure, making the entanglement of SPI and LS tighter, thereby improving the mechanical properties of protein-based materials.

[0090] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-toughness soy protein isolate composite film, characterized in that: The following steps are involved: Step 1: Mix 2 g of soy protein isolate, 0.2 g of sodium lignin sulfonate and 30 mL of deionized water in a 50 mL flask, place in a 90 ° C water bath and stir, adjust the pH to 9 with sodium hydroxide solution, add 0.4 mL of glycerol, maintain a constant temperature of 90 ° C and stir for 1 hour, and then cool the water bath naturally; Step 2: When the temperature in the water bath is cooled to 45°C, 0.4 g of urea is added for modification, and the mixture is stirred at a constant temperature of 45°C for 1 hour; Step 3: Pour the obtained soy protein isolate solution into a 10*10*0.8cm 3 The mixture was placed in a silicone mold and dried naturally to obtain a soy protein isolate composite film.

2. The method for preparing the high-toughness soy protein isolate composite film according to claim 1, characterized in that: The concentration of the NaOH is 1-1.5 mol / L.

3. A composite membrane, characterized in that The high-toughness soy protein isolate composite film is prepared by the preparation method of any one of claims 1 to 2.

Citation Information

Patent Citations

  • Soybean separation protein / cellulose mixed solution, and preparation method and use thereof

    CN101168603A

  • Modified soybean protein plastic and its prepn. and use

    CN1362451A